Female circumcision or female genital mutilation? An Islamic viewpoint - Mohd, Azizah; Alkali, Alhaji Umar (2014)
The practice of female circumcision pre-dates Islam. The Jews and the Coptic Christians in Egypt are known for this practice. The basis for female circumcision is basically the Sunnah of the Prophet pbuh, the tradition from the compilation of Abu Dawood. The Muslim scholars that see no wrong in female circumcision themselves approve of the practice when it is done in such a manner that does not cause harm or danger to the female child. This also reflects that female circumcision in Islamic perspective is totally different from female genital mutilation as practiced in certain cultures. Under no circumstance is a person allowed to cause harm to another under Islamic law, hence the practice of female genital mutilation that causes harm to a female child is haram and does not have any backing from the Qur’an, hadith, Ijma and other sources of Islamic law. This paper wishes to examine female circumcision and female genital mutilation in Islam as to whether it is part of a religious act or merely cultural practice. This paper intends to expose the position of Islamic law on female circumcision in line with the fact that such practice has a far-reaching negative effect on the physical and psychological wellbeing of the female child. It equally intends to table the views of Muslim scholars on the practice. Finally, the paper will examine the practice of female circumcision in Malaysia. It is believed that the findings will be beneficial to all researchers, students, legal fraternity, and the public as a whole.